Burkina Faso : Policies to Protect the Poor From the Impact of Food and Energy Price Increases - Adenauer, Isabell (IMF Working Papers; Working Paper ;, 2011)
This paper assesses the effectiveness of policies taken by the Burkinabe authorities to protect the poor from the adverse impact of a combined food and oil price shock in 2008. Estimates of the impact based on household survey data and a price pass-through model suggest that these policies were not well-targeted, benefiting the wealthier groups of the population rather than the poor. More effective policy measures, such as a conditional cash transfer system, which is already being implemented on a pilot basis in urban areas, are discussed as an alternative policy option.